Genetic variability and heritability in broad bean collections from central Mexico - Oliveros-González, María Teresa; Pérez-López, Delfina de Jesús; González-Huerta, Andrés; Ramírez-Dávila, José Francisco; Flores-Carrera, Laura Stephanie (Revista Mexicana de Ciencias Agrícolas, 2025)
This work was conducted with the aim of estimating variance components and broad sense heritabilities (H2) in quantitative and qualitative traits in 25 cultivars of broad beans using an experimental design of randomized complete blocks with four replications in a series of trials. The differences between the two environments (A), the 25 genotypes (G), and their interaction were significant for most of the traits evaluated. The highest H2 ranged from 51.73 to 96.68%. Principal component analysis accounted for 63.62% of the original total variation, yield was positively and significantly correlated with EFFI, NPP, PD, PL, WP, and YIE. The prediction with the GAM indicated that with NPP, PD, WP, and YIE, there would be greater genetic progress by selection. There was little phenotypic variability within each of the qualitative traits.